IRIGASI TETES HOMEMADE PENGHEMAT AIR BAGI WARGA PERUMAHAN VILLA BOUGENVILLE INDAH KECAMATAN SUMBERSARI KABUPATEN JEMBER - Ilham Muhklisin; Putri Santika (Bajang Institute, 2022)
The problem of water scarcity, especially during dry season often occurs in Indonesia. Urban activities such as irrigation for gardening are usually carried out in a wasteful manner. In addition, other problems such as household waste, especially plastic bottles, also need to be a concern. The purpose of this community service was to introduce a water saving irrigation namely drip irrigation sytem to to residents of the Villa Bougenville Indah housing estate, Antirogo sub-district, Sumbersari District, Jember Regency, East Java Province of Indonesia. A simple homemade drip irrigation device made from materials such as plastic bottles and infusion hoses was introduced to them through extension activities (direct home visits). This activity was positively responded by the residents. Some residents have succeeded in making and using drip irrigation in their homes. It is hoped that citizens' awareness and concern for the importance of saving air and maintaining environmental cleanliness can continue to increase.